KESANTUNAN BERBAHASA PADA KOMENTAR YOUTUBE CHANNEL REFLY HARUN DENGAN TOPIK JAKARTA TIDAK BANJIR 2021 - Mujiyanto Mujiyanto; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is entitled language politeness on Refly Harun's Youtube channel comments with the topic of Jakarta not flooding 2021. The purpose of this study is to describe comments that are in accordance with the principle of language politeness and that violate the principle of language politeness. The method used is a descriptive-synchronous method by describing qualitative data. Furthermore, the results of this study found 27 utterances that were in accordance with the adherence to the principle of language politeness and 9 violations of the principle of language compliance from a total of 225 data. The principle of politeness in question includes: (A) maxim of wisdom 2 data, (B) maxim of generosity of 2 data, (C) maxim of awarding 10 data, (D) maxim of simplicity of 1 data, (E) maxim of manufacturing of 2 data, and (F) maxim of sympathy of 10 data. violations of the principle of language compliance include: (A) 5 data discretion maxim, (B) 3 data award maxim, and (C) 1 data sympathy maxim.Keywords: adherence to the principle of civility, violation of the principle of civility, comments